"El Niño 1997-98": its effect on environment and fishery resources in Peru - Espino, Marco (1999)
It is presented a review of "El Niño 1997-98" effects on fishery resources of Peruvian upwelling ecosystem, given emphasis to the changes in distribution and abundance patterns of anchovy, sardine, and Peruvian hake; and autecology changes of the same resources. Finally, it is analyzed similarities and differences of this phenomenon effect with other events of the same nature.